How Can Social Media Be Helpful for Immigrants to Integrate Society in the US - Erdem, Bora (European Journal of Multidisciplinary Studies, 2018)
With an increase in diversity in the society, the United States has been faced with the challenge of how to integrate its immigrants in the American communities. Different researches have shown that social media has a significant role in the integration of these immigrants. However, that which has been missing in such studies encompasses the conceptual frameworks for understanding the existing interplay between the utilization of social media and, on the other hand, integration. The results of this research point out that social media has a significant relevance in the participation of immigrants in acquiring language, cultural competencies and bridging social capital. Based on these results, therefore, an analysis of immigrant integration in American by using social media has been demonstrated in the paper.